Characterising COVID-19 school and childcare outbreaks in Canada in 2021: a surveillance study - Kaitlin Patterson; Erin McGill; Demy Dam; Anna Bellos; Cameron Mark Coulby; Rachel McCormick (BMJ Publishing Group, 2024)
Background In January 2021, the Public Health Agency of Canada launched the Canadian COVID-19 Outbreak Surveillance System to monitor outbreaks by setting. Schools and childcare centres were identified as settings of interest, as children play a key role in the transmission chain of other respiratory illnesses. This paper describes outbreak trends observed in school and childcare settings from January to December 2021 when many public health measures were in place.Methods School and childcare outbreak data from five jurisdictions were included, representing 76% of the total Canadian population. Epidemiological curves were generated, trends in outbreak settings and cases' age distribution over time were examined and descriptive statistics on outbreak size were calculated.Results In 2021, most school and childcare outbreaks were in primary schools (42%). Severity was low in school and childcare settings (0.40% of outbreak cases hospitalised, <0.01% of outbreak cases deceased). Most school and childcare outbreaks reported fewer than 10 cases per outbreak. During the start of the 2021-2022 school year (September 2021), there were fewer outbreaks in secondary schools and fewer cases among those aged 12+ years compared with January-June of 2021.Conclusion During the study period, there was no observed association between an increase in school and childcare outbreaks and an increase in incidence rates in community case data. Children remain a population of interest for SARS-CoV-2; however, severity in paediatric populations remained low throughout 2021 and the risk of transmission in Canadian schools was low.